Laparoscopic cholecystectomy in intrahepatic gallbladder: a case report - González, Yazmin G.; Hernandez, Reyger G.; Cen, Cristina Uxul (International Journal of Research in Medical Sciences, 2024)
Variations in the location of the gallbladder are absence of the gallbladder, location on the left side, intrahepatic (the most common located in the right hepatic lobe) and mobile gallbladder, these anomalies increase the risk of gallstone formation. 22-year-old female, presents symptoms of diffuse abdominal colic pain in the epigastrium and right hypochondrium exacerbated by the consumption of cholecystokinetic foods, physical examination without alterations, laboratories without alterations, ultrasound of the liver and bile ducts reports a gallbladder of small diameters. and presence of lithiasis, subtotal cholecystectomy was performed laparoscopically, leaving the transhepatic segment and resecting supra- and infra-vesicular portions. The intrahepatic vesicle is an anomaly in vesicular development and migration in embryogenesis. This anomaly increases the predisposition to stone formation due to alteration in vesicular motility secondary to incomplete emptying. Since there are no clinical or paraclinical changes, it tends to be underdiagnosed and becomes a challenge for the clinician. The infra and suprahepatic portion was dissected, the intrahepatic portion was not resected, where no complications occurred and it evolved from satisfactorily in subsequent appointments.